Diagnóstico de la calidad del servicio del área de Dirección de Gestión Ambiental e Higiene del Gobierno Autónomo Descentralizado cantón Rocafuerte - Carvajal Zambrano, Sandra Marcela (2021)
The purpose of this research work was to diagnose the quality of service in the area of Environmental Management and Hygiene Management for the improvement of the attention of the users of the Decentralized Autonomous Government of the Rocafuerte canton. In the development of the research process, the following methods were applied: inductive, deductive and descriptive, which allowed us to identify the services provided by the study area. The techniques used were the interview and survey, the same ones that gave greater support to the work. The SERVQUAL model was also applied, the main results were that 73% of the sample totally agreed with the technological equipment used in the agency, 67% totally disagreed that the facilities were not suitable to provide a good service to citizens, while 77% mentioned that they did not agree or disagree regarding the time saved to obtain a satisfactory service. On the other hand, it was concluded that it is necessary for the municipal council to consider the improvement plan proposal in order to correct the shortcomings found in the investigation, as well as carry out similar studies in other agencies with the intention of optimizing institutional processes.